New genetic tools for plant defense against parasitic nematodes - A. V. Kochetov; T. A. Gavrilenko; O. S. Afanasenko (Вавиловский журнал генетики и селекции)
Nematodes belong to economically important pests. Here we reviewed the recent data on molecular mechanisms of plant resistance to cyst and gall nematodes including the most devastating Globodera rostochiensis, G. pallida, Heterodera schachtii, Meloidogyne chitwoodi, and M. incognita. The Golden Potato Cyst Nematode (G. rostochiensis, GPCN) may be taken as an example of an economically important pest: in Russia, it occurs in 61 regions with a total area of 1.8 million ha and may cause the yield loss from 19 to 90 %. The biological characteristics of sedentary nematodes makes their agrotechnical control problematic, i.e. the GPCN cysts remain dormant in soil for many years until a susceptible host appears, whereas nematicides are either toxic or inefficient. Introgression of resistance genes (R-genes) from related cultivated or wild species is likely to be the most appropriate way for their biocontrol. The life cycle of sedentary nematodes is based on juveniles’ penetration into the host root where they reprogram plant cells into a syncytium or the so-called ‘giant cells’ and inhibit the plant defense response. Molecular mechanisms of plant-nematode interaction are unusual and this phenomenon provides a very interesting model for the investigation of plant morphogenesis control as well as for the development of new genetic instruments of biocontrol. Here we reviewed recent publications on plant parasitic nematode effectors used for hijacking of the plant immune system, data on R-genes and molecular mechanisms of their activities. In addition, host-induced gene silencing (HIGS) is discussed as a perspective mechanism for nematode biocontrol. HIGS is based on the RNA interference in the cells of the host plant addressed against the nematode genes important for their development and productivity. Several recent investigations demonstrated efficiency of HIGS against sedentary nematodes.